The empirical foundation of the golden rule - Elías, Víctor (Estudios de Economía, 2016)
This paper analizes with cross-sectional data if the Golden Rule condition satisfies: where the saving index is equal to capital (beta) or to the real interest rate, equal to the gross output growth of households.